IoT Light Switch Project in Smart Home to Enhance Concept Mastery of Vocational High School Students - Wulandari, Catur; Purwaningsih, Endang; Parno, Parno (Jurnal Ilmiah Pendidikan Fisika, 2024)
This research aims to improve vocational school students' mastery of dynamic electricity through STEM-PJBL learning in the TPACK framework. This dynamic electrical material is important for vocational school students in Technology and Information expertise because it is the basis for productive vocational learning at the next level. Facts in the field show that the mastery of the concept of vocational school students still needs to improve. Thus, to increase the mastery of the concept, a web-based interactive media, Google Sites, was used with a student project to prototype an IoT light switch on a smart home. This study is a pseudo-experimental research with a pretest-posttest group design with 32 students in class X TJKT. The results of this study show that STEM-PJBL learning in the TPACK framework can significantly increase concept mastery (sig 2-tailed < 0.05) with Ngain by 0.59.